2019
DOI: 10.3390/ma12111868
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Spark Plasma Sintered Si3N4/WC Ceramic Tools

Abstract: Silicon nitride (Si3N4) based ceramic tools exhibit good machinability in cutting materials such as gray cast iron, ductile iron, malleable cast iron, and superalloys due to excellent high-temperature mechanical properties. In this paper, high-performance Si3N4-based ceramic tools containing tungsten carbide (WC) and cobalt (Co) were studied. Effects of the WC content and Co content on mechanical properties and a microstructure of Si3N4-based ceramic materials were analyzed. Results showed that Si3N4-based cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Among these, Si 3 N 4 ceramics are widely utilized as cutting tool materials due to the high hardness, high strength, and high thermal shock resistance 7–9 . In the field of cutting machining, Si 3 N 4 ‐based ceramic cutting tools are commonly employed for machining superalloy 10 and cast iron 11 materials. Si 3 N 4 ‐based tools exhibit the potential for machining ductile cast iron due to their superior wear resistance and comprehensive mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Si 3 N 4 ceramics are widely utilized as cutting tool materials due to the high hardness, high strength, and high thermal shock resistance 7–9 . In the field of cutting machining, Si 3 N 4 ‐based ceramic cutting tools are commonly employed for machining superalloy 10 and cast iron 11 materials. Si 3 N 4 ‐based tools exhibit the potential for machining ductile cast iron due to their superior wear resistance and comprehensive mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, much research [ 31 , 32 , 33 ] has indicated that the bimodal distribution [ 34 ] of Si 3 N 4 ceramics with more columnar β-Si 3 N 4 grains is advantageous to improve the strength and toughness by introducing low-cost β-Si 3 N 4 [ 35 ] whiskers [ 27 ] and/or seeds [ 36 ]. In addition, generally, various reinforced particles such as TiC [ 37 ], TiN [ 5 , 27 ], Ti(C, N) [ 11 ], WC [ 38 ], SiC [ 4 ] and graphene [ 39 ] are also mixed into Si 3 N 4 -based ceramics [ 35 ] to enhance their properties. For example, graphene [ 21 , 32 , 39 ] was used to reinforce a Si 3 N 4 ceramics matrix, from which the fracture toughness was markedly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…1) [5,6].The authors have taken advantage of such a decomposition to prepare WC-W 2 C composite at three different compositions by arc plasma melt casting of W and WC pellets prepared from their powder mixture mixed at different proportions. The mono carbide of tungsten (WC) characterized with superior properties like high melting point (2750 °C) and high hardness (16)(17)(18)(19)(20)(21)(22) [7][8][9]. Kim and co-workers [10] reported hardness of binderless WC to be 2486 VHN with 97.6 relative density (%).…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten carbide used in producing critical components such as spray injection nozzle, sand blasting nozzle, guide sleeve in machines, micrometre anvil, centre for lathe and grinder, rock cutting drill bit, etc. [12][13][14][15][16][17][18]. Applications of tungsten carbide metal matrix composites are found in the mining industry to coat different drilling and digging parts, in agriculture for coating on plough shares, tillage equipment and cutters.…”
Section: Introductionmentioning
confidence: 99%